Membangun Konsep Dasar Manajemen Pendidikan dengan Metode Mind Mapping pada Mahasiswa Tahun I Program Studi Manajemen Pendidikan Islam STAIN Mandailing Natal - Defi, Wahyu Fitrina (STAIN Madina Press, 2020)
The learning transformation at this recent days and it’s move from 4.0 to 5.0 area make every education institution should always upgrade with various developments in science and technology, if it’s not able to adjust to the pace of the movement, educational institutions are prepared to be unable to achieve their goal in a certain phase later. Beside that the learning methods should always be upgraded too. Mindmapping method is a method that can create creativity and mindset of students and they will be able to build their understanding of certain concepts. This research is a qualitative research with a case study approach. Data in this research was collected by observation, interview, and documentation study. Data were analyzed through three stages: data reduction, data presentation, and conclusion. Informant research are the first Islamic Educational Management Study Program students at STAIN Mandailing Natal with the three subject matter, they are organizational management at the first semester, schools management at the second semester. The findings of this research are: 1) The process of applying the mindmapping method, 2) Problem and solutions encountered in applying the mindmapping method